Cerebrospinal fluid dynamics along the optic nerve - Sheng, Jinqiao; Li, Qi; Liu, Tingting; Wang, Xiaofei (Frontiers in Neurology, 2022)
The cerebrospinal fluid (CSF) plays an important role in delivering nutrients and eliminating the metabolic wastes of the central nervous system. An interrupted CSF flow could cause disorders of the brain and eyes such as Alzheimer's disease and glaucoma. This review provides an overview of the anatomy and flow pathways of the CSF system with an emphasis on the optic nerve. Imaging technologies used for visualizing the CSF dynamics and the anatomic structures associated with CSF circulation have been highlighted. Recent advances in the use of computational models to predict CSF flow patterns have been introduced. Open questions and potential mechanisms underlying CSF circulation at the optic nerves have also been discussed.